2015
DOI: 10.1021/jm5017413
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Novel Antagonists to the Human Neurokinin-3 Receptor for the Treatment of Sex-Hormone Disorders (Part I)

Abstract: Neurokinin-3 receptor (NK3R) has recently emerged as important in modulating the tonic pulsatile gonadotropin-releasing hormone (GnRH) release. We therefore decided to explore NK3R antagonists as therapeutics for sex-hormone disorders that can potentially benefit from lowering GnRH pulsatility with consequent diminished levels of plasma luteinizing hormone (LH) and correspondingly attenuated levels of circulating androgens and estrogens. The discovery and lead optimization of a novel N-acyl-triazolopiperazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 70 publications
7
36
0
Order By: Relevance
“…NK3R antagonist pharmacology on ovarian hormones is explained in the context of drug effects in the arcuate nucleus modulating GnRH pulse frequency, a concept consistent with our findings on the LH pulse frequency, the differential effects on LH and FSH in intact females, and the importance of adequate potency-normalized, free drug concentrations in brain and plasma to achieve in vivo efficacy (11,13). However, it is noted that NKB/NK3R mRNA is also expressed in human mural granulosa cells (54) and the myometrium (55), with significantly elevated expression in leiomyomas (eg, uterine fibroids, [56]).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…NK3R antagonist pharmacology on ovarian hormones is explained in the context of drug effects in the arcuate nucleus modulating GnRH pulse frequency, a concept consistent with our findings on the LH pulse frequency, the differential effects on LH and FSH in intact females, and the importance of adequate potency-normalized, free drug concentrations in brain and plasma to achieve in vivo efficacy (11,13). However, it is noted that NKB/NK3R mRNA is also expressed in human mural granulosa cells (54) and the myometrium (55), with significantly elevated expression in leiomyomas (eg, uterine fibroids, [56]).…”
Section: Discussionsupporting
confidence: 79%
“…Previously we have reported that the peripheral administration of NK3R antagonists, including ESN364, decreases plasma LH levels in castrate rat and monkey in a manner demonstrating a clear correlation between pharmacodynamics (PD) and pharmacokinetics (PK) of potency-normalized free drug concentrations in the plasma and brain, respectively (11,13). Here we extend these findings by demonstrating in OVX ewe that the diminution of plasma LH levels is specifically due to an interruption of the LH pulse.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Numerous studies indicated that the function of NK3R related to tachykinins exert a plethora of biological effects, including smooth muscle contraction and relaxation, vasodilatation, secretion, activation of the immune system, pain transmission and neurogenic inflammation, and are implicated in a broad range of CNS disorders [27, 28]. Here, we described further evidence that NKB could function as an endogenous angiogenesis inhibitor.…”
Section: Discussionsupporting
confidence: 55%
“…Due to the spacial similarity of vinyl groups to ring embedded sulfur atoms thiadiazoles can be considered isosteres of diazines 5,6 adding to their potential to serve as fragments of bioactive structures. [7][8][9][10] Thiadiazoles can occur in four distinct regioisomeric forms (1)(2)(3)(4) enriching their structural diversity with respect to local polarization and vector space occupied by both carbon bound substituents R 1 and R 2 ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%